Peran Guru dalam Pemanfaatan Gawai untuk Meningkatkan Pembelajaran di Masa Pandemi - Sri Prabandari; Salamah Salamah (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to determine the benefits of gadgets in learning during a pandemic. This study uses a qualitative approach. The research method is literature and literature study. The results of this study show that the use of gadgets in online learning has benefits in the world of education during the pandemic. The positive impact of children being able to interact with friends wherever they are, being able to learn online in a pandemic situation, while the negative impact of children is more often playing gadgets than playing with the environment so that children will become individualists. The teacher's role in learning during the pandemic is to design and implement android-based learning, supported by the role of parents of students.